The social well-being of people with restricted life space - Anna A. Dargan (Социологический журнал, 2015)
The article presents the results of empirical studies of the peculiarities of the social well-being of people with restricted life space depending on the chosen (paternalistic or social) model of disability. This social phenomenon is considered to be the most important part of disabled people’s perception of the world (including individual identity) comprising the following: regarding themselves as disabled people, awareness/unawareness of the fact that disability status is/is not officially acknowledged, awareness of their own intellectual, emotional and physical capacities, having an idea of ways and opportunities to satisfy their basic needs as well as forms of and prospects for their integration into the society.There are objective and subjective factors that influence the social well-being of people with restricted life space and their interaction with the society. The dominant factors in the social well-being of the representatives of this social group include unavailability of accomodation and the lack of rehabilitation facilities for disabled people; acquisition of professional education, employment prospects for disabled people, limited opportunities for satisfaction of their social and cultural needs.The empirical data are used to show that difficulties which a person with restricted life space faces are social problems that result from unequal relationships between disabled people and the rest of society, the unwillingness of the society to take into account the special needs of disabled people.The typology of social behaviour of people with restricted life space is introduced, the following criteria being used: the model of disability chosen by an individual, the attitude of a disabled person to his own disability as well as an active / passive approach to implementation of the strategy for integration into the society.